Analisis Tata Kelola Pelaksanaan Pemilu 2019 di Kabupaten Gunungkidul Indonesia - Andang Nugroho; Achmad Nurmandi; Suranto Suranto; Salahudin Salahudin (Journal of Government and Civil Society, 2020)
Simultaneous elections in 2019 have been held successfully. Where legislative members, presidents and vice presidents for the period 2019-2024 have been appointed. However, of course in the stages of the implementation of the election process there are obstacles faced by all parties involved in the election, be it the organizer of the election itself, political parties, the community or other stakeholders such as local governments and security elements. Discrete qualitative research is used in this study to describe the problems that occur from the perspective of election actors in Gunungkidul Regency. The research is limited only to actors from the community, stakeholders, political parties, Regency KPU and Regency Bawaslu. The data source was taken from minutes of meetings and coordination conducted by the KPU of Gunungkidul Regency from 2017 to 2019 added with news about the election in Gunungkidul on online media. Then the NVivo12 Plus software is used in data analysis techniques by using the crosstab feature to show the problems obtained. The results obtained that each actor has different intensity in assessing problems in the implementation of elections. The problems that arise are more on the interests of these actors in the implementation of the ongoing elections. The contribution of this research is on the assessment of each actor in seeing the election problems that are taking place. Studies on this issue need to be carried out with various sources to make it more comprehensive. Pemilu serentak pada 2019 telah berhasil dilaksanakan. Di mana anggota legislatif, Presiden dan Wakil Presiden untuk periode 2019-2024 telah dilantik. Namun demikian tentu saja pada tahappelaksanaan proses pemilu ada kendala yang dihadapi oleh semua pihak yang terlibat dalam pemilu, baik itu penyelenggara pemilu itu sendiri, partai politik, masyarakat atau pemangku kepentingan lainnya seperti pemerintah daerah dan elemen keamanan. Penelitian kualitatif deskriptif digunakan dalam penelitian ini untuk menggambarkan masalah yang terjadi dari perspektif aktor pemilu di Kabupaten Gunungkidul. Penelitian ini terbatas hanya untuk aktor dari masyarakat, pemangku kepentingan, partai politik, KPU Kabupaten dan Bawaslu Kabupaten. Sumber data diambil dari risalah notulen rapat dan koordinasi yang dilakukan oleh KPU Kabupaten Gunungkidul dari 2017 hingga 2019 ditambah dengan berita tentang pemilihan di Gunungkidul pada media online. Kemudian software NVivo12 Plus digunakan dalam teknik analisis data dengan menggunakan fitur crosstab untuk menunjukkan masalah yang diperoleh. Hasil yang diperoleh bahwa masing-masing actor memiliki intensitas yang berbeda dalam menilai masalah dalam pelaksanaan pemilu. Masalah yang muncul lebih pada kepentingan aktor-aktor ini dalam pelaksanaan pemilu yang sedang berlangsung. Kontribusi dari penelitian ini adalah pada penilaian masing-masing aktor dalam melihat masalah pemilu yang sedang berlangsung. Studi tentang masalah ini perlu dilakukan dengan berbagai sumber untuk membuatnya lebih komprehensif.